2020
DOI: 10.1249/mss.0000000000002278
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Vaccination after Training: Immune Response and Side Effects in Athletes

Abstract: Objectives Influenza vaccination was used to assess whether induction of immunity or side effects are influenced by the timing of the last training session before vaccination. Methods Forty-five healthy athletes (36 male, 23 ± 8 yr, ≥5 training sessions per week, predominantly national competition level) were vaccinated with the tetravalent influenza vaccine; blood samples were collected immediately before and 1, 2, and 26 wk after vaccination. Athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Athletes are recommended to receive all necessary vaccines before competition due to increased risks of viral exposure ( 10 ). A recent study in elite German athletes found that the quadrivalent inactivated influenza vaccine evoked a strong immune response with no reported side effects or loss of training ( 11 ). However, due to emerging reports (albeit mostly anecdotal) of adverse symptoms associated with COVID-19 vaccines, there is a growing concern among the athletic community that vaccination might hinder athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes are recommended to receive all necessary vaccines before competition due to increased risks of viral exposure ( 10 ). A recent study in elite German athletes found that the quadrivalent inactivated influenza vaccine evoked a strong immune response with no reported side effects or loss of training ( 11 ). However, due to emerging reports (albeit mostly anecdotal) of adverse symptoms associated with COVID-19 vaccines, there is a growing concern among the athletic community that vaccination might hinder athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recommended that elite athletes receive all necessary vaccines prior to competition due to increased risks of viral exposure (7). A recent study in elite German athletes of 10 different types of sport found that the quadrivalent inactivated influenza vaccine (a synthetic vaccine consisting of four inactivated influenza viruses) elicited a strong immune response one week after vaccination with no reported side-effects or loss of training (8). However, due to increasing reports (albeit mostly anecdotal) of adverse symptoms associated with COVID-19 vaccines, there is a growing concern among the athletic community that vaccination might hinder athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Special vaccination guidelines for elite athletes have been suggested in order to adjust to specific needs, for example, before travelling to endemic areas (Gärtner and Meyer 2014). And it has been shown recently that there is neither some kind of 'immunosuppression' from long-term elite training nor an acute influence from training sessions on vaccination effectiveness (Ledo et al 2020;Stenger et al Forthcoming). Albeit without experimental evidence, it is plausible to assume that professional football training, as it is commonly performed in these days, does not impair immune function relevantly, either.…”
Section: Prevention Of Infectious Diseasesmentioning
confidence: 99%